The Effect of CSR and Consumer Satisfaction on Customer Loyalty and Customer Trust in Sharia Banks - Alvianto Putra Ardiansyah; Muchsin Muthohar (Jurnal Economic Resource, 2023)
Corporate Social Responsibility which is a social responsibility to the community and Customer Satisfaction in achieving its goals, one of which is consumer loyalty or Customer Loyalty which is influenced by Customer Trust based on the Theory of Sustainability on Marketing That is when companies maintain their consumer status in the business world. The purpose of this study was to determine the effect of the relationship between hypotheses on the services provided from banking companies from previous research gaps. The object of research focuses on banking companies with the subject of all customers of Bank Syariah Indonesia. This study used Structural Equation Modeling (SEM) with 220 respondents who were distributed through questionnaires. Test drive with IBM SPSS 22 program. The results of this study show Corporate Social Responsibility to Customer Loyalty directly or mediated by Customer Trust, as well as Customer Satisfaction which has a positive influence on Customer Loyalty directly or mediated by Customer Trust.